Estratégias para mitigar as emissões de NH3, N2O e CH4 em compostagem automatizada de dejetos líquidos de suínos - Giacomini, Diego Antonio (2017)
Gaseous losses during composting of pig slurry (PS), mainly due to volatilization of ammonia (NH3), emission of nitrous oxide (N2O) and methane (CH4) have important environmental and economic implications, requiring technological alternatives for their mitigation. The objective in the study was to evaluate strategies to reduce gaseous nitrogen (N) and carbon (C) losses during the automated composting of PS. Two experiments were performed: the first in pilot scale with duration of 21 days, to select the most efficient additive in the NH3 mitigation for later use, which evaluated the use of zeolite, biochar and retorted shale (RS) in the 20% dose, to PS, on a substrate consisting of sawdust and shavings, with three applications of PS + additives followed by stirring, in addition to three additional treatments; and another in 245 days automated composting platform consisting of three treatments: PS, PS + RS and PS + RS + dicyandiamide (DCD), this one in line contained 1.250 kg of substrate. And 10.150 L of DLS, 825 kg of RS and 16,5 kg of DCD were added at substrate, divided into 15 applications in respective treatments. The reduction in NH3 emissions was of 36% when evaluated with XR use, in both experiments. The addition of DCD to DLS was only effective in reducing N2O emissions during the first 53 days of composting, increasing emissions thereafter. At the end of the experiment, the cumulative emission of N2O increased by 120% with the use of DCD. The addition of XR in DLS there was a reduction in CH4 emission between 64 and 74%, probably as a function of the reduction of the pH of the compound.